Prohibited Covenants in Insurance - an Analysis of Abusive Clauses Relating to Reimbursement for Renting a Car Based on the UOKIK's Chairman's Decisions - Karpińska, Marta (Studia Oeconomica Posnaniensia, 2015)
The introduction of prohibited covenants, thanks to the widened scope of the register of prohibited clauses constitutes an effective tool to combat practitioners denying the interests of consumers. Ensuring effective protection is especially important in case of third parties, meaning that the injured party which would not have any influence on the shaping of its entitlements without the UOKIK intervention. The author has analyzed prohibited covenants indicated in the SOKIK sentence handed down in Warsaw in December 2013 by the UOKIK Chairman on the insurance company PZU S.A. supporting the decision to impose a penalty for applying prohibited clauses in insurance contracts The clauses concerned the disadvantageous procedure to the customer of the repayment of costs for the hire of a substitute car for the injured parties and the damage which the car experienced as the result of a collision. The author has presented and justified three theses. Firstly - one should grant the injured party the status of the consumer which enables the application of the regulations intended for consumer protection before the application of negative collective interests and potential UOKIK intervention. Secondly - the loss of the possibility of use of the damaged vehicle is a damage to property. Thirdly - in case of the lease of a substitute car the reimbursement of costs should concern the actual period, in which the injured party cannot use the damaged vehicle, rather than only the period taken for the repair . It is worthwhile noticing that the acceptance by UOKIK and SN the pro-consumer interpretation can cause a significant inflow of claims from injured consumers demanding from the insurance company the repayment of the cost of the substitute hired car.